Technology vs. government : the irresistible force meets the immovable object - Levine, Lloyd (Studies in media and communications, 2024)
Governmental entities in the United States have multiple, well publicized failures and challenges when it comes to procuring and integrating new technologies. A quick search will yield a treasure trove of technology procurement and implementation gone wrong. Projects seem to routinely suffer from significant cost overruns, poor fit, and implementation delays. Additionally, while the private sector keeps pace with technology changes and improvements, the government lags behind when it comes to integrating and deploying new technologies. Technology vs. Government examines why government fails at technology acquisitions, innovation, and implementation, the impact on people, and the future opportunities and implications for government service, administration and policy. Underlying the issues discussed in the book is the question of Generation T, a term coined in this book to define the generation born in 2002 and later. Generation T is the first generation to grow up in a societal technology bubble. Their first response in most situations is to reach for technology. How will they work for and interact with government if government doesn't have the same technology first mindset? Analyzing the relationship between the government in the US and technological adoption, this volume of Studies in Media and Communications provides lessons and principles that are applicable to governments with western-style democracies or similar forms of administration.